Female maturation and rematuration acceleration of Mutiara strain catfish (Clarias gariepinus) using combination of oocyte developer hormone and astaxanthin addition diet - Jufri, Fatahillah Maulana; Sudrajat, Agus Oman; Setiawati, Mia (Indonesian Society of Scientific Aquaculture (ISSA), 2019)
ABSTRACT Reproductive design for gonadal maturation process mostly related with some factors such as environmental signals, reproductive organs, hormonal and nutrition. This research was conducted on female Mutiara strain of North African Catfish, Clarias gariepinus by combining two kinds of materials administered to broodstock diet, namely oocyte developer (Oodev) which contains of PMSG hormone and antidopamin, and astaxanthin carotenoid. Research designs were divided into C (Control), A50 (astaxanthin 50 mg/kg feed), A100 (astaxanthin 100 mg/kg feed), Od0.5 (Oodev 0.5 mL/kg fish for two weeks), Od1 (1 mL/kg fish for 2 weeks), Od0.5A50 (combined Od0.5 with A50), Od1A50 (combined Od1 with A50), Od0.5A100 (combined Od0.5 with A100), and Od1A100 (combined Od1 with A100). This research was performed during twelve weeks of feeding. The Od1A100 treatment showed the best reproduction performance result compared to other treatment with highest hepatosomatic (HSI) and gonadosomatic (HSI) indexes (P<0.05), also fastest increase in egg diameters (P<0.05), shorter rematuration periods and highest proportion of mature broodstock. These results indicated that Oodev and astaxanthin could accelerate gonadal maturity in female broodstock of Mutiara catfish.Keywords: Broodstock, hormonal, reproduction, oocyte developer, astaxanthin ABSTRAK Rekayasa reproduksi untuk proses pematangan gonad sebagian besar terkait dengan beberapa faktor seperti sinyal lingkungan, organ reproduksi, hormonal dan nutrisi. Penelitian ini dilakukan terhadap strain ikan lele Mutiara (Clarias gariepinus) betina menggunakan dua bahan yang dicampur pada pakan induk, yaitu oocyte developer (Oodev) yang mengandung hormon PMSG dan antidopamin, dan karotenoid astaxanthin. Eksperimen yang dirancang adalah K (Kontrol), A50 (Astaxanthin 50 mg/kg pakan), A100 (Astaxanthin 100 mg/kg pakan), Od0.5 (Oodev 0,5 mL/kg induk untuk 2 minggu), Od1 (Oodev 1 mL/kg induk untuk 2 minggu), Od0.5A50 (kombinasi Od0.5 dan A50), Od1A50 (kombinasi Od1 dan A50), Od0.5A100 (kombinasi Od0.5 dan A100), dan Od1A100 (kombinasi Od1 dan A100). Penelitian ini dilakukan dengan memberi makan dua belas minggu. Performa reproduksi terbaik didapat pada perlakuan Od1A100. Od1A100 memiliki indeks hepatosomatik (HSI) dan gonadosomatik (HSI) tertinggi (P <0,05), juga diameter telur paling cepat besar (p <0,05), periode rematurasi terpendek, dan proporsi induk matang gonad tertinggi. Hasil ini menunjukkan bahwa Oodev dan astaxanthin dapat mempercepat kematangan gonad pada induk betina ikah lele Mutiara. Keyword: Induk, hormon, reproduksi, oocyte developer, astaxanthin